(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Drought impacts various physiological processes in plants, ultimately affecting yield. The study aimed to determine the influence of drought stress on the fruit and yield quality of three different varieties of tomato namely; Rio, Dan Syria and UTC. The plants were subjected to four treatments which were subjected to 80-85% WHC (water holding capacity) (control, T1), 55-60% WHC (light drought stress, T2), 40-45% WHC (moderate drought stress, T3) and 30-35% WHC (severe drought stress, T4) and each replicated three times. The data generated were subjected to Analysis of Variance (ANOVA). According to the findings, Rio outperformed the other varieties in terms of fresh fruit weight (21.59g), fruit pericarp thickness (3.96mm) and drought tolerance index (56.17%) under severe drought conditions. However, under severe drought conditions, the highest average number of fruits (2.33) was produced by the UTC, closely followed by Dan Syria (2). The results also showed that under severe drought stress, Rio outperformed the other varieties in terms of fresh and dry weight of shoot, as well as fresh and dry weight of root (18.82g, 3.47g and 3.34g, 1.29g) closely followed by Dan Syria measuring 12.47g, 1.66g, 3.10g, and 0.62g respectively. Under conditions of severe drought stress, Rio, UTC, and Dan Syria exhibit drought tolerance indices of 56.17%, 37.49%, and 20.44% respectively. These suggest that Rio is the most resilient to drought compared to the other varieties. Therefore, farmers should consider using Rio, which has a high level of drought resistance, as a means to mitigate the impact of drought.